Design approach for FRP spike anchors in FRP-strengthened RC structures. (15th April 2019) - del Rey Castillo, Enrique; Kanitkar, Ravi; Smith, Scott T.; Griffith, Michael C.; Ingham, Jason M.
Abstract: The strength and deformability of reinforced concrete (RC) structures strengthened with externally bonded fibre-reinforced polymer (FRP) composites can be enhanced with the addition of anchorage devices. The inclusion of anchorage can also result in a higher utilization of the desirable strength properties of the FRP by mitigating debonding. FRP spike anchors are a particularly effective type of anchorage devices as they can be applied to a wide variety of structural forms that have been strengthened with FRP composites. Experimental verification has supported the effectiveness of such anchors. However, the limited availability of design guidance is inhibiting the widespread application of anchors in practice. A critical review of the design models available in the literature is presented in addition to a design methodology for the incorporation of FRP spike anchors in RC structures strengthened with FRP composites. Exemplar designs of FRP spike anchors are also presented, to be used in combination with the design examples currently included in ACI 440.2R (2017). Finally, several knowledge gaps are identified which can be used to inform future studies.